Incidence of fires and related injuries after giving out free smoke alarms: cluster randomised controlled trial. Issue 7371 (2nd November 2002) - DiGuiseppi, Carolyn; Roberts, Ian; Wade, Angie; Sculpher, Mark; Edwards, Phil; Godward, Catherine; Pan, Huiqi; Slater, Suzanne
Abstract: Objective: To measure the effect of giving out free smoke alarms on rates of fires and rates of fire related injury in a deprived multiethnic urban population. Design: Cluster randomised controlled trial. Setting: Forty electoral wards in two boroughs of inner London, United Kingdom. Participants: Primarily households including elderly people or children and households that are in housing rented from the borough council. Intervention: 20 050 smoke alarms, fittings, and educational brochures distributed free and installed on request. Main outcome measures: Rates of fires and related injuries during two years after the distribution; alarm ownership, installation, andfunction. Results: Giving out free smoke alarms did not reduce injuries related to fire (rate ratio 1.3; 95% confidence interval 0.9 to 1.9), admissions to hospital and deaths (1.3; 0.7 to 2.3), or fires attended by the fire brigade (1.1; 0.96 to 1.3). Similar proportions of intervention and control households had installed alarms (36/119 (30%) v 35/109 (32%); odds ratio 0.9; 95% confidence interval 0.5 to 1.7) and working alarms (19/118 (16%) v 18/108 (17%); 0.9; 0.4 to 1.8). Conclusions: Giving out free smoke alarms in a deprived, multiethnic, urban community did not reduce injuries related to fire, mostly because few alarms had been installed or were maintained.